Publication Trends in Indonesian Language Teaching: Focus on 'Making Effective Sentences' (2014-2023) - Addy Septyawan; Dwi Rohman Soleh; Sigit Ricahyono (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research analyzes publication trends and collaboration dynamics in the development of Indonesian language teaching materials with a focus on learning to make effective sentences. The research method used is bibliometric analysis, which examines publication trends from 2014 to 2023. The data collection technique utilizes the. Dimension  AI database to gather publications spanning the 2014-2023 period, with a focus on employing bibliometric analysis techniques such as citation analysis to evaluate the scholarly impact and interconnectedness of research works within the specified timeframe. This research identifies a significant increase in research interest in the topic in 2015, followed by a subsequent decline until 2023, prompting further exploration of the underlying reasons and implications for the field. Network analysis of authors and organizations unveiled significant collaboration, with Surabaya State University emerging as a pivotal hub facilitating cohesive research efforts, suggesting its distinctive contributions or influence on shaping the field warrant further exploration. In addition, keyword cluster analysis identifies eight primary research focuses, encompassing motivation, games, hypno teaching, media development, learning models, and creative thinking skills, furnishing crucial insights for crafting Indonesian language teaching materials tailored to enhance sentence learning effectiveness, creativity, and relevance, thereby fostering more engaging and impactful educational experiences.